The Issue of Synonymy between the Words Al-Hulm and Al-Ru’ya in Surah Yusuf: A Quranic Semantics Study - Al Farabi, Fahmi Akhyar; Sabilul Wafda (Journal of Arabic Language Studies and Teaching, 2023)
The issue of synonymy in the Holy Qur'an is one of the important controversial issues between scholars and those working with the Qur'an and its sciences, ancient and modern. Some scholars prove the occurrence of synonymy in the Qur'an by the difference in the two words and the meaning being the same, and some of them deny its occurrence by the complete lack of synonymy between the two words. It is one of the synonymous words in the Qur'an, including Al-Hulm and Al-Ru'ya. This study aims to clarify and answer detailed implications in the meaning of the words Al-Hulm and Al-Ru'ya in Surah Yusuf. The type of this study is a desk study to obtain facts about the semantic meaning between these two words using the descriptive and analytical approach to solve study problems. The results of this research are that the semantic study reveals great secrets and wondrous wisdom that can only be imagined by those who contemplate this great miracle of the Qur'an. The words al-Hilm and al-Ru'ya have synonymy and context comparison. Regarding synonymy, these two words have the same meaning: dream. Meanwhile, in a comparative context, the verses in al-Ru'ya show dreams and are revelations sent down by Allah SWT to His Prophet and can be interpreted. As for al-Hilm in context, it has no meaning and does not require interpretation, and it is associated with Satan, and it is not permissible for Muslims to talk about it because it is part of Satan's play.